IMPLEMENTASI SISTEM E-FILLING DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS KANTOR PELAYANAN PAJAK PRATAMA BADUNG SELATAN) - Wahyuningsih, Evi (CITIZEN CHARTER, 2017)
E-filling system is a realization of government programs to help individual taxpayers or corporate taxpayers to carry out their obligations. E-filling system has been implemented and required to all taxpayers in indonesia since 2014. During the second (2) years of implementation, the use of e-filling system in submitting annual SPT such as has been running quite well, but if viewed from the number of annual notification that entered throught the e-filling system, the number is still not able to improve compliance from individual taxpayers to the maximum. E-filling system only can used by individual taxpayers that know internet and individual taxpayers who have a simple and very simple SPT form. This study must be have an porpuse, the purpose is to invertigate the implementation of e-filling system and obstacles in the implementation of e-filling system. The study used a descriptive qualitative research methodology. In obtaining primary data, the author directly to the field. While to get secondary data, the author use study documentation. And the author also use interviews directly in this study. This study have a conclusion, the conclusion e-filling sytem has been good, but has not been able to improve individual taxpayers compliance to the maximum due to lack of socialization and awareness of individual taxpayer. The obstacles that must be overcome is the socialization is not evenly distributed, the taxpayers do not know the internet and long queue when searching e-fin. Keywords : public policy implementation, public policy, e-filling system